Exploring Value Propositions to Drive Self-Sovereign Identity Adoption - Lockwood, Mick (Frontiers in Blockchain, 2021)
This paper presents research exploring the balancing of interactive friction and value proposition in the context of Self-Sovereign Identity (SSI) technology adoption. This work extends a related investigation of a full agency engagement with a User-Centred Data Ecosystem (UCDE) utilising what is described as a Sovereign Boundary Mechanism (SBM). An SBM is a standardised collection of SSI interactions, which can collectively be described as a metaphorical ring of sovereignty between the participant and the wider network. Within this model participants control identity, relationships, credentials, data streams, and access control. This related work concludes that the developing trend poses significant interactive friction, and that clear and substantive value proposition would be required to drive and sustain participant adoption. This paper explores potential value propositions for SSI, considering theory relating to Privacy, Surveillance Capitalism, and Human Data Interaction; in parallel opinions are drawn from the thematic analysis of interviews with experts in the decentralised field and results from a public survey. This research concludes that the value proposition is unlikely to come from the direct perceived protection of privacy. Also, that the decentralised technologies cannot be marketed solely on the fact that it is decentralised. Instead, value will emerge from the capability of SSI functionality to supersede the centralised model, offering innovation and reduced transactional friction across individual, business and wider society. This research suggests that the SSI community needs to develop a cohesive design strategy, a clear narrative and vocabulary. Value needs to be defined across cultural context, while targeting accessible, high value niche opportunities to build momentum towards sustainable adoption.